The SAGE handbook of feminist theory - Evans, Mary (SAGE reference, 2014)
At no point in recorded history has there been an absence of intense, and heated, discussion about the subject of how to conduct relations between women and men. This Handbook provides a comprehensive guide to these omnipresent issues and debates, mapping the present and future of thinking about feminist theory. The chapters gathered here present the state of the art in scholarship in the field, covering: Epistemology and marginality; Literary, visual and cultural representations; Sexuality; Macro and microeconomics of gender; Conflict and peace. The most important consensus in this volume is that a central organizing tenet of feminism is its willingness to examine the ways in which gender and relations between women and men have been (and are) organized. The authors bring a shared commitment to the critical appraisal of gender relations, as well as a recognition that to think ‘theoretically’ is not to detach concerns from lived experience but to extend the possibilities of understanding. With this focus on theory and theorizing about the world in which we live, this Handbook asks us, across all disciplines and situations, to abandon our taken-for-granted assumptions about the world and interrogate both the origin and the implications of our ideas about gender relations and feminism. It is an essential reference work for advanced students and academics not only of feminist theory, but of gender and sexuality across the humanities and social sciences.
Keywords: approches et analyses; corps; cours; discipline; har4600; histoire et politique; intersectionnalité; outils; ouvrages de références; philosophie; phénoménologie; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences de la gestion; sciences humaines; sciences sociales; sex1911; thématiques; violences; économie; épistémologie; études féministes

Blanches et Noires : histoire(s) des Américaines au XIXe siècle - Lehuu, Isabelle (Cahiers de l'IREF, 2011)
«Les chapitres qui suivent mettent en lumière tant la parole des femmes que le discours sur les femmes, les actions et les représentations. Ils explorent la réalité quotidienne de femmes ordinaires du XIXe, jeunes et moins jeunes, mariées et célibataires, blanches et noires, au Nord comme au Sud, qui sont restées silencieuses, souvent dans l’ombre d’un mari, d’un père ou d’un maître. Leurs témoignages, les mots qu’elles ont laissés dans les sources publiques et privées, les gestes qu’elles ont posés aussi bien dans le cadre de leurs relations affectives qu’au sein de leur exploitation familiale, leur réseau social, leur travail, leur église, leur communauté urbaine ou villageoise, leur région, sont autant d’indices à décoder pour dresser un portrait nuancé et documenter la condition des femmes aux États-Unis dans toute sa diversité sociale et culturelle.»
Keywords: 1800-1899; afro-féminisme; amériques; approches et analyses; black feminism; cours; discipline; esclavagisme; femmes* blanches; femmes* noires; féminisme afroaméricain; féminismes noirs; his4443; histoire; histoire des femmes*; intersectionnalité; justice sociale; militance; mouvement aboitionnisme; philosophie politique; premier cycle; privilèges; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; états-unis; états-unis (sud); études féministes